STUDY REGARDING THE INFLUENCE OF PERIODONTAL MAINTENANCE THERAPY ON TOOTH SURVIVAL IN PATIENTS WITH REMOVABLE PARTIAL DENTURES - Ciocan-Pendefunda Arina; Ursarescu-Sufaru Irina Georgeta; Martu-Stefanache Maria Alexandra; Ioanid Nicoleta; Mârțu Ioana; Pendefunda Valeria; Iftene Gabriela (Romanian Society of Oral Rehabilitation, 2017)
Aim: Removable partial dentures (RPDs) can influence the oral health and have the potential to cause further tooth loss, especially of abutment teeth. However, no evidence indicates the effective interval of regular periodontal maintenance after RPD provision. This study aimed to examine the impact of regular periodontal maintenance visits on survival of RPD abutment teeth. Materials and Methods: Patients were included if they had been provided with a clasp-retained RPD and had used it for 2 years or more. According to the frequency of periodontal maintenance, study samples were divided into three groups; every 3-6 months (3-6M) group, 1-year (1Y) group and no-maintenance (NM) group. Results: Five-year cumulative survival rates were 82.6% (3-6M), 74.4% (1Y) and 70.8% (NM) respectively. Survival of abutment teeth in the 3-6M group was significantly better than both 1Y and NM groups. Conclusion: The periodontal maintenance at least once in 6 months had the most favorable outcome. Frequent periodontal maintenance after RPD provision could be effective in preventing further tooth loss.